Agroecosystems : - Krishna, K. R. (Apple Academic Press, 2014)
Agroecosystems of the World Agroecosystems: An Introduction Soils of Agroecosystems Wheat Agroecosystem Maize Agroecosystem Wet Land Rice Agroecosystem Sorghum Agroecosystem of Asia, Africa and Americas Finger Millet Cropping Zones of Asia and Africa Minor Cereals and Millets Soybean Production Zones Lentil Cropping Belts Chickpea Cropping Zones Cowpea Farming Zones of Africa and Asia Pigeonpea Agroecosystem of Asia, Africa and Caribbean Islands Black Gram and Green Gram Belts Horse Gram Cropping Zones of Asia and Africa Canola Cropping Zones Groundnut Agroecosystem Sunflower Agroecosystem Minor Oilseeds Cotton Cropping Zones Sugarcane Producing Zones Forages and Pastures Plantations Crops of the World Principles of Nutrient Dynamics Atmosphere Influences Nutrient Dynamics in Agroecosystems Nutrient Supply into Agroecosystem Nutrient Transformations in Arable Cropping Systems Nutrient Transformations in Flooded Wetland Belts Nutrient Recovery by Crops Nutrient Loss from Agroecosystems Nutrient Cycling in Crop Fields Factors Influencing Nutrient Dynamics in Agroecosystems Soil Tillage and Mulches Affect Nutrient Dynamics Soil Organic Matter and Nutrient Dynamics Soil Microorganisms and Nutrient Dynamics in Agroecosystems Weeds and Nutrients in Agroecosystems Irrigation Systems Influence Nutrient Dynamics in Agroecosystems Crops, Genotypes and Nutrient Dynamics within Agroecosystems Cropping Systems and Nutrient Dynamics Index